The Fight for Balkan Latinity. The Aromanians until World War I. - Motta, Giuseppe (Richtmann Publishing, 2011)
The Aromanians of Vlahs are a people of the Balkans historically mentioned in many sources and documents thruoughoutthe centuries, since the age of Roman colonization. Their particular identity emerged during the XIX century, when the rise ofnationalism involved also the Vlahs, who demanded the protection of the Sultan against Greek propaganda and denationalizationpolicies. Also the newborn State of Romania was interested in their situation and started a diplomatic controversy with Greece to defendBalkan latinity. The question gained relevance during the age of the Balkan Wars (1912-1913) and the first World War, when thearrival of Italian troops in the region of Pindus was welcomed by the Aromanians who welcomed Italian army and appealed to thecommon Latin inheritance for the defense of their national specificity and traditions.